Odpowiedzi

2009-11-30T18:33:27+01:00
A)2x( do kwadratu) -x +14x -7= 2x( do kwadratu) + 13x -7
b) 2a (do kw) +8a-a-4= 2a (do kw) + 7a-4
c) 8a-12a(do kw) -2 +3a= 11a-12a(do kw) -2
d)x(do kw) -√5x + √5x -5= x( do kw) - 5
e) 2y( do kw) +2y - √3y - √3= 2y( do kw) + (2 - √3)y - √3
f)a( do kw) - √3a + √2a - pierwiastek z 6= a( do kw) - (√3+ √2)a - pierwiastek z 6
g) 4 - 2√2k + √2k-k( do kw)= -k(do kw) +4 - ( 2√2+ √2)k
2009-11-30T18:37:15+01:00
A) (x + 7)(2x - 1)=
2x²-7
b) (2a - 1)(a + 4)=
2a²-4
c) (4a - 1)(2 - 3a)=
8a²+3a
d) (x + √5)(x - √5)=
x²-√25=x²-5
e) (2y - √3)(y + 1)=
2y²-√3
f) (a + √2)(a - √3)=
a²-√6
g) (2√2 + k)(√2 - k) =
4-k²